E-learning content design standards based on interactive digital concepts maps in light of meaningful learning theory and constructivist learning theory - Mohammed Afify (OmniaScience, 2018)
The present study aims to identify standards of interactive digital concepts maps design and their measurement indicators as a tool to develop, oraganize and administer e-learning content in the light of Meaningful Learning Theory and Constructivist Learning Theory. To achieve the objective of the research, the author prepared a list of E-learning content design standards based on interactive digital concepts maps. It involved (11) general standards and (40) performance indicators. It was investigated by 21 teaching staff members who are experts in educational technology and e-learning to ration the list and its performance indicators. Results illustrated that standards are too significant and appropriate for the purpose of the study. Results were discussed in the light of theoretical background results of researches and literature review in the field. The study provided recomendations and suggestions that can be used as practical applications in the field of developing E-learning content based on utilizing interactive digital concepts maps.